Potential Of Using Abai’s Poetic Corpara for Research, Educational and Methodical Purposes - K.K., Pirmanova; A.D., Serikbayeva; N.М. Nurlybayev; D.A., Sabirova (Journal of Ecohumanism, 2024)
The article describes the goals and objectives of creating national language corpora and their educational potential. The creation of Abai’s poetic corpora, the potential of the poetic corpora in solving research, educational and methodological problems is described as part of the research carried out by the authors.The article contains a demonstration of the capabilities of national language corpora, including poetic sub-corpora. The latter, from the authors’ point of view, can become a tool for studying both the theory and history of literature, the author’s style, the system of artistic images, means of expression and poetic syntax, rhythm, meter, rhyme, etc.As a potential for using the national corpora in general and the poetic corpus in particular, the authors name a conceptual analysis of the author’s poetic text, determining the “attraction” or “repulsion” of a lexeme to a metrical structure, identifying moments of intertextuality, searching and analyzing moments of homonymy, synonymy, antonymy, polysemy and etc.The article highlights different points of view on the possibilities of using the resources of national language corpora, including polar ones. The authors offer specific tasks for practicing various skills in teaching language and literature.The authors conclude that the poetic corpus of Abai as part of the National Corpora of the Kazakh language in the future opens up wide opportunities for linguistic and literary studies, preservation of the cultural and linguistic fund, as well as opportunities for use in the process of teaching language and literature by both native speakers and foreigners.